The Effect of Using Augmented Reality in Science Learning on Middle School Students' Concept Understanding - Sutarman, Asep; Chan, Levina; S., Antoni (PT. Technology Laboratories Indonesia (TechnoLabs), 2024)
This study aims to explore the effect of using Augmented Reality (AR) technology in science learning on secondary school students' concept understanding. AR technology allows the integration of the virtual world with the real world through interactive and dynamic visualization, so it is expected to increase learning interest and understanding of science concepts among students. The method used in this study was a quasi-experiment with a pretest-posttest control group design. The research sample consisted of 120 grade X students in one of the secondary schools who were randomly divided into experimental and control groups. The experimental group used AR application as part of science learning, while the control group used conventional methods. Data were collected through concept understanding tests administered before and after the intervention. The results of the data analysis showed that there was a significant increase in the concept understanding of students using AR compared to the control group. The mean posttest score of the experimental group was statistically higher than that of the control group (p < 0.05). This finding indicates that the use of AR in science learning is effective in improving students' concept understanding. This study suggests that AR technology can be integrated into the science learning curriculum as an innovative and effective tool. In addition, further research is recommended to explore other aspects of using AR in education as well as its impact on students' cognitive and affective skills.